2021
DOI: 10.3390/genes12020151
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Anomalies in USH2A Cause Central Auditory Anomalies in a Mouse Model of Usher Syndrome and CAPD

Abstract: Central auditory processing disorder (CAPD) is associated with difficulties hearing and processing acoustic information, as well as subsequent impacts on the development of higher-order cognitive processes (i.e., attention and language). Yet CAPD also lacks clear and consistent diagnostic criteria, with widespread clinical disagreement on this matter. As such, identification of biological markers for CAPD would be useful. A recent genome association study identified a potential CAPD risk gene, USH2A. In a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…These motifs have been most commonly observed in the protein components of the basal laminin, extracellular matrixes, and cell adhesion molecules (Bhattacharya and Cosgrove, 2005). Genetic in vivo studies have shown that usherin is essential for the survival of photoreceptor cells and inner ear hair cell bundle integrity (Zou et al, 2011;Perrino et al, 2021;Schwaller et al, 2021). Although these studies above provide clues for uncovering the functions of the USH2A gene, however, its large size and broad spectrum of mutations raise many challenges for researchers to develop effective gene therapy (Stemerdink et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These motifs have been most commonly observed in the protein components of the basal laminin, extracellular matrixes, and cell adhesion molecules (Bhattacharya and Cosgrove, 2005). Genetic in vivo studies have shown that usherin is essential for the survival of photoreceptor cells and inner ear hair cell bundle integrity (Zou et al, 2011;Perrino et al, 2021;Schwaller et al, 2021). Although these studies above provide clues for uncovering the functions of the USH2A gene, however, its large size and broad spectrum of mutations raise many challenges for researchers to develop effective gene therapy (Stemerdink et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 19 21 Variable effects on respiratory cilia 22 and fertility 23 have been reported. Some hypomorphic genetic variants can cause non-syndromic RP (e.g., USH2A is also the most frequent cause of nonsyndromic AR-RP) 24 , 25 and may cause isolated deafness (e.g., in MYO7A, USH1C, CDH23, PCDH15 ) even when monoallelic, 26 28 further compounding the diagnostic complexity. The characteristics and severity of the phenotype depend on the position and degree of deleteriousness of the causative variant.…”
mentioning
confidence: 99%
“…Perrino et al employed the mouse to model the potential role of USH2A defects in central auditory processing disorder (CAPD), as was indicated in a genome-wide association study (GWAS) [19]. The authors indeed obtained indications for an effect of Ush2a defects on the structure of the central auditory system, both in homozygous knockout as well as heterozygous knockout mice.…”
mentioning
confidence: 99%